Aplikasi Pengenalan Plat Nomor Kendaraan Negara Indonesia Menggunakan Metode Support Vector Machine (SVM) - Timothy Tamara; Rudy Adipranata; Rolly Intan (Jurnal Infra, 2019)
The license plate recognition system is one of the techniques of licence plate data handling through the use of image processing. This research is divided into two parts, namely the methods of training and the license plate recognition using SVM classification. The early image processing involves the preprocessing stage continued by locating the license plate and segmenting every character on it. The segmented characters will be processed further with SVM. Test results show a success where the accuracy rate of the plate recognition reaches 79.64%.